2006
DOI: 10.1623/hysj.51.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Global effects of doubled atmospheric CO2 content on evapotranspiration, soil moisture and runoff under potential natural vegetation

Abstract: Rising atmospheric CO 2 concentration affects the water balance through climatic changes and through changes in transpiration, vegetation structure and distribution. This study quantifies CO 2 effects upon evapotranspiration, soil moisture and runoff under conditions of potential natural vegetation globally, using a biosphere model forced by observed climate . Isolated CO 2 impacts were inferred from a 2 × CO 2 scenario, assuming no climate change. Global effects are moderate: evapotranspiration reduces by 7%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 44 publications
(51 reference statements)
5
63
0
Order By: Relevance
“…Although studies with equilibrium vegetation models suggested that increased leaf area may offset stomatal closure (Betts et al, 1997;Kergoat et al, 2002), studies with dynamic global vegetation models indicate that the effects of stomatal closure exceed those of increasing leaf area. Taking into account CO 2 -induced changes in vegetation, global mean runoff under a 2×CO 2 climate has been simulated to increase by approximately 5% as a result of reduced evapotranspiration due to CO 2 enrichment alone (Leipprand and Gerten, 2006;Betts et al, 2007). [WGII 3.4.1]…”
Section: Evapotranspirationmentioning
confidence: 99%
“…Although studies with equilibrium vegetation models suggested that increased leaf area may offset stomatal closure (Betts et al, 1997;Kergoat et al, 2002), studies with dynamic global vegetation models indicate that the effects of stomatal closure exceed those of increasing leaf area. Taking into account CO 2 -induced changes in vegetation, global mean runoff under a 2×CO 2 climate has been simulated to increase by approximately 5% as a result of reduced evapotranspiration due to CO 2 enrichment alone (Leipprand and Gerten, 2006;Betts et al, 2007). [WGII 3.4.1]…”
Section: Evapotranspirationmentioning
confidence: 99%
“…The water cycle controls the distribution and productivity of terrestrial vegetation (Stephenson 1990;Churkina et al 1999), and in turn, the vegetal cover type is a key determinant for evapotranspiration and global runoff (Dunn and Mackay 1995). The runoff is constrained by vegetation through stomatal conductance (Field et al 1995;Morison and Gifford 1983), root pattern, leaf area (Milly 1997;Betts et al 1997), interception and transpiration (Leipprand and Gerten 2006;Beaulieu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on modelling or experimental methods showed that stomatal conductance may decrease by as little as 25% (Field et al 1995) or as much as 40% (Morison and Gifford 1983;Luo et al 2013), since plants tend to close their stomata to maintain an optimal balance between water loss and CO 2 absorption (Van de Geijn and Goudriaan 1997;Woodward 2002). Under a doubled CO 2 concentration, global evapotranspiration is predicted to decrease by 7%, while runoff and soil moisture are predicted to increase by 5 and 1%, respectively (Leipprand and Gerten 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The parameter k 13 is held constant at 29 ppm throughout. Although the expression for CO 2 fertilisation parameterises the uncertain saturating increase in gross primary productivity (GPP) under elevated CO 2 , the simplified moisture balance formulation does not capture the changes in evapotranspiration, soil moisture and run-off due to the physiological effect (Leipprand and Gerten, 2006;Betts et al, 2007).…”
Section: P B Holden Et Almentioning
confidence: 99%